2020
DOI: 10.1136/bcr-2019-232714
|View full text |Cite
|
Sign up to set email alerts
|

Isolated unilateral proximal focal femoral deficiency presenting in a young woman

Abstract: Proximal focal femoral deficiency (PFFD) is a rare congenital skeletal abnormality characterised by the partial absence of the proximal femoral segment with shortening of the entire lower extremity. It typically presents as a shortened thigh, which is flexed, externally rotated and abducted. Some other skeletal anomalies, especially fibular hemimelia, usually accompany the disorder. The diagnosis of PFFD is made in early childhood and based mainly on conventional radiography. However, the radiographic appearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 9 publications
(14 reference statements)
0
19
0
Order By: Relevance
“…Lengthening is dependent on discrepancy at maturity. If the discrepancy at maturity is less than 20 cm and the hip and knee joint are stable, then limb lengthening procedures are recommended [4] . This was the scenario in our case where shortening was 4.5cm, and lengthening was done in order to improve the child's ambulatory skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lengthening is dependent on discrepancy at maturity. If the discrepancy at maturity is less than 20 cm and the hip and knee joint are stable, then limb lengthening procedures are recommended [4] . This was the scenario in our case where shortening was 4.5cm, and lengthening was done in order to improve the child's ambulatory skills.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital femoral insufficiency includes different types of anomalies ranging from the dysplastic hip with a relatively normal femur and shortening of the femur to the most critical condition of total absence of femur [2] . Proximal femoral focal deficit (PFFD), also known by the term congenital proximal femoral deficit (CPFD), is an uncommon congenital skeletal disorder defined as a shortening of the lower extremities due to incomplete absence of the proximal femoral segment [3,4] . The etiology of PFFD is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Also in the current literature, few cases of PFFD were diagnosed in adulthood. Özdemir et al 24 reported isolated unilateral PFFD presenting in a young woman. Many risk factors for PFFD were documented in the literature such as hypoxia, ischemia, diabetes mellitus, irradiation, chemical toxins, microbiological agents, and hormones.…”
Section: Discussionmentioning
confidence: 99%
“…starting from dysplastic hip with relative normal femur, shortening femur, and most severe form which is total absent of femur with only distal femoral condyles present [1]. Proximal femoral focal deficit (PFFD), likewise acknowledged as congenital proximal femoral deficit (CPFD) is an unusual congenital skeletal disorder well-defined by the incomplete nonappearance of the proximal femoral segment with shortening of the entire lower extremities [1,2]. The incidence varies from 1 case per 50,000 people to 1 case per 200,000 people [2].…”
Section: Introductionmentioning
confidence: 99%
“…Proximal femoral focal deficit (PFFD), likewise acknowledged as congenital proximal femoral deficit (CPFD) is an unusual congenital skeletal disorder well-defined by the incomplete nonappearance of the proximal femoral segment with shortening of the entire lower extremities [1,2]. The incidence varies from 1 case per 50,000 people to 1 case per 200,000 people [2]. At one time, Proximal Femoral Focal Deficiency turn out to be sorted with other disorders, like coxa vara and short bowed femurs, which led to misperception and misinterpretation.…”
Section: Introductionmentioning
confidence: 99%